Women’s refuge a protection and recovery shelter for abused women with physical disabilities - Importante, Florentina Mae M.
Victims of violence and sexual abuse continue to increase, and victims seek services and support from shelters. In the Philippines, the lockdown due to the Covid-19 pandemic imposed strict restrictions that caused economic and social challenges for Filipino women, more so for women with disabilities, which led to a rise in violence and sexual abuse cases. Fortunately, there are shelters that provide assistance for victims who are women with disabilities in the Philippines. However, service providers avoid giving special treatment to women with disabilities as they believed this is discrimination against them. Furthermore, the lack of understanding of their needs and the differences in their experiences from those without disabilities lead to inefficient service and design that is unsuitable for the efficient and speedy recovery and treatment of these victims (Lee, Devine, Marco, Zayas, Gill-Atkinson, & Vaughan, 2015). Thus, this project aims to identify spatial features that are necessary for a shelter in the treatment of women with physical disabilities, specifically those with visual, hearing, speech, and mobility impairments, who are victims of violence and sexual abuse; examine programs that can be added to a shelter’s services for the victim’s well-being and growth; contribute to the body of knowledge on architectural design approaches to improve further the inclusive and adaptive design in shelters for victims of violence and sexual abuse, specifically for women with physical disabilities who are seeking support and services for their treatment and recovery in the Philippines, that can be a useful resource for architects, designers, planners, and policy-makers who are conceptualizing design responses; develop an architectural space programming specifically for the victims’ rehabilitation and treatment based on findings and research on their additional needs as people with physical disabilities; with the information gathered, design a women’s refuge that serves as a protection and recovery shelter for women with physical disabilities in the Philippines.